Grasses and Grassland New Perspectives - Aamir Iqbal, Muhammad (IntechOpen, 2022)
Grasslands are of vital significance globally by covering more than one-quarter of the earth's surface. They are known by a variety of names, such as prairies, pampas, steppes, savannas, and so on, and provide feed to animals as well as serve as biodiversity reserves and catchment areas. Under the changing climate scenario, they can potentially serve as carbon sinks, which might alleviate the adverse effects of greenhouse gas emissions. This book provides fundamental knowledge of underutilized grasses of economic significance as well as discusses advancements in grasslands management for boosting their bio-productivity. There is a particular focus on state-of-the-art strategies for the restoration and conservation of grasslands in the era of changing climate.